Q: Silpilify the expression -2b -6 plus 3b -2?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

5b + 11 - 2b = 3b + 11

6b^2 - 3b / 3b 6b^2 - 1 or ( 6b^2 - 3b) / 3b = 2b - 1 Or (6b^2 - 3b ) / 3b = 3b(2b - ) / 3b = 2b - 1

5+3b? :3

It is: b+4 when simplified

In hexadecimal, 2B16 + 3B16 = 6616

Related questions

-2b + 7 -3b = 2 -2b +7 -3b +2b = 2 + 2b 7 -3b + 3b = 2 + 2b +3b 7-2 = 2-2 + 2b + 3b 5 = 5b 1 = b

8b + 11 - 3b = 2b + 2 5b + 11 = 2b + 2 5b - 2b = 2 - 11 3b = -9 b = -3

The equation (b2 - 2b) + (3b - 6) = b2 + b - 6

5b + 11 - 2b = 3b + 11

-2a plus 3b

6b^2 - 3b / 3b 6b^2 - 1 or ( 6b^2 - 3b) / 3b = 2b - 1 Or (6b^2 - 3b ) / 3b = 3b(2b - ) / 3b = 2b - 1

3a - 2b

5b plus 5-3b-7 is 2b-2.

It simplifies to: 3b+17

5+3b? :3

4a + 3c - 2b - c + a - b = 5a - 3b + 2c

It is: b+4 when simplified